Post mortem lost of texture of fish meat during cold storage (2007)
This work is a review on the conformation and importance of connective tissue of fish meat. The post mortem softening of fish meat as a quality factor is influenced by the characteristics of the collagens present in each species. The degradation of collagen appears to be related to freezing. By biochemical analysis as well as electronic microscopy many researches have demonstrated that the loss of texture is related to pericelular connective tissue degradation. Currently some post crop practices are proposed to reduce this phenomenon.